2016
DOI: 10.1021/acs.jafc.6b00462
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Methylation in Arabidopsis thaliana Expressing an Algal Arsenite Methyltransferase Gene Increases Arsenic Phytotoxicity

Abstract: Arsenic (As) contamination in soil can lead to elevated transfer of As to the food chain. One potential mitigation strategy is to genetically engineer plants to enable them to transform inorganic As to methylated and volatile As species. In this study, we genetically engineered two ecotypes of Arabidopsis thaliana with the arsenite (As(III)) S-adenosylmethyltransferase (arsM) gene from the eukaryotic alga Chlamydomonas reinhardtii. The transgenic A. thaliana plants gained a strong ability to methylate As, conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Another promising strategy is based on expressing the arsenate efflux transporter from yeast ( Saccharomyces cerevisiae ) in rice, which can reduce arsenic accumulation in brown rice by 20%. A less successful idea to methylate sodium arsenite to DMA by expressing an algal arsM gene in Arabidopsis resulted in lethal phytotoxicity 205 , suggesting that arsenic methylation in plants can only be an effective detoxification strategy if volatile arsines are the end point of the methylation.…”
Section: Limiting Arsenic Uptake By Cropsmentioning
confidence: 99%
“…Another promising strategy is based on expressing the arsenate efflux transporter from yeast ( Saccharomyces cerevisiae ) in rice, which can reduce arsenic accumulation in brown rice by 20%. A less successful idea to methylate sodium arsenite to DMA by expressing an algal arsM gene in Arabidopsis resulted in lethal phytotoxicity 205 , suggesting that arsenic methylation in plants can only be an effective detoxification strategy if volatile arsines are the end point of the methylation.…”
Section: Limiting Arsenic Uptake By Cropsmentioning
confidence: 99%
“…Thus DMAs(V) builds up and is only slowly methylated a third time to the volatiles species TMAs(III). This interpretation is supported by the observation that Chlamydomonas reinhardtii has only limited ability to volatilize As (Tang et al 2016b). The efficiency of As methylation and volatilization varies widely among different microorganisms (Qin et al 2009; Qin et al 2006; Wang et al 2014; Zhang et al 2015), possibly due to differences in microbial growth and the catalytic ability of ArsM enzymes.…”
Section: Discussionmentioning
confidence: 64%
“…DMAs(V) is highly mobile during the root to shoot translocation (Li et al 2009; Raab et al 2007; Tang et al 2016a; Ye et al 2010), so it is possible that methylated As species produced in the nodules are efficiently transported to the above ground tissues with little retention in roots. For example, Tang et al (2016b) showed that transgenic A. thaliana expressing CrarsM contained most DMAs(V) in the shoots but very little DMAs(V) in the roots, suggesting that DMAs(V) had been efficiently transported to the shoots.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations